Allometry of the secondary sexual characters of the shore crab Pachygrapsus transversus (Gibbes, 1850) (Brachyura, Grapsidae) - Flores, A.; Negreiros-Fransozo, M. L. (Brill Academic Publishers, 1999)
The allometric growth of secondary sexual characters in Pachygrapsus transversus is investigated from the 2(nd) crab stage onward. Clear sexual dimorphism is restricted to abdominal morphology, but ANCOVA analyses showed that chelae become larger in males and the carapace becomes wider in females. Size at the puberty moult in both sexes was estimated using Somerton's computer techniques. Mature II analyses applied to bi-log gonopod length vs, carapace length relationships indicated a puberty moult at 5.0 mm in males.In females, Mature I analyses detected the overlapping growth phase lines in bi-log carapace length vs. abdomen width scatterplots. Fitting the logistic equation provided an estimate of 50% maturity at 5.5 mm. The regression lines separate young and resting individuals from the potentially reproductive females, but they do not separate young from adult crabs. Year-round monthly samples showed that the proportion of small adult-like females is higher during the breeding season. After breeding, females may moult to a young-like morphotype, as observed in controlled laboratory conditions. Moulting to a resting condition splits smaller mature females into different growth phase lines. Therefore, estimates of female size at sexual maturity by means of abdomen allometric growth analyses are inadequate in this species.